2013
DOI: 10.1038/jid.2013.55
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of mtDNA Damage Elicited by Oxidative Stress in the Arsenical Skin Cancers

Abstract: Arsenic causes several human cancers. Arsenic-induced Bowen's disease (As-BD), the most common arsenical cancer, is characterized by increased proliferation, dysplasia, and individual cell apoptosis, all of which involve mitochondria. We reported that arsenic causes aberrant keratinocyte proliferation through mtTFA-mediated mitochondrial biogenesis in As-BD. Increasing mitochondrial biogenesis causes cells to undergo oxidative stress. However, how arsenic induces oxidative stress and causes mtDNA damage in ars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 47 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…6,15 In skin, 8-OHdG expression is induced by UVR in normal human epidermis 16 and increased in arsenic-induced BD. 17 We document that 8-OHdG is overexpressed in AK and BD tissue compared with adjacent non-lesional tissue, healthy controls and SCC.…”
Section: Discussionmentioning
confidence: 75%
“…6,15 In skin, 8-OHdG expression is induced by UVR in normal human epidermis 16 and increased in arsenic-induced BD. 17 We document that 8-OHdG is overexpressed in AK and BD tissue compared with adjacent non-lesional tissue, healthy controls and SCC.…”
Section: Discussionmentioning
confidence: 75%
“…Arsenite was previously reported to diminish cellular antioxidant responses [ 31 ], which would also result in formation of more 8oxoG. Recent studies have however suggested that arsenite exposure at concentrations similar to ours may cause some increase in gene expression levels of DNA repair enzymes such as the 8oxoG repair enzyme human 8-oxoguanine DNA N-glycosylase 1 (hOGG1) [ 10 ]. Arsenic-induced ROS are also thought to contribute to PARP-1 inhibition and subsequent impairment of DNA repair [ 32 ].…”
Section: Discussionmentioning
confidence: 76%
“…No skin cancers developed in unirradiated, arsenic-exposed mice [ 9 ]. Furthermore, in humans, arsenic-induced Bowen’s disease contained higher levels of 8oxoG compared to non arsenic-induced Bowen’s disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies have proven that arsenic induces oxidative stress and DNA damage. Arsenic increases DNA 8-hydroxy-2'-deoxyguanosine (8-OHdG) levels in mouse urothelium [ 12 , 30 ] as well as enhances oxidative stress and 8-OHdG levels in the mitochondria DNA of keratinocytes [ 31 ]. BBN also increases DNA 8-OHdG levels and arsenic has an additional effect on mouse urothelium [ 12 ].…”
Section: Discussionmentioning
confidence: 99%